Transformasi Kebijakan Pekerjaan dan Penghidupan Layak: Kajian Literatur tentang Upaya Negara dalam Memenuhi Hak Warga Negara melalui Implementasi Undang-Undang Cipta Kerja - Mustikarini, Indriyana Dwi (LP. Ma'arif Janggan Magetan, 2023)
This study aims to examine the Job Creation Law and the concept of Omnibus Law in Indonesia with a focus on harmonization of labor regulations, the process of law formation, and implementation at the regional level as well as legal protection for Micro, Small and Medium Enterprises (MSMEs). The research methods used are juridical normative and descriptive qualitative, with data collection through analysis of legal documents. The results showed weaknesses in harmonization of labor regulations, non-conformity in the process of forming the Job Creation Law with laws and regulations, as well as good governance but needed to overcome obstacles at the regional level. Legal protection for MSME actors in the Job Creation Law shows potential effectiveness, but needs further evaluation. This research recommends review and improvement in the formulation and implementation of regulations to achieve better results and in accordance with strong legal principles in Indonesia.